A long range, energy efficient internet of things based drought monitoring system - Van-Phuc Hoang; Minh-Hong Nguyen; Thanh Quan Do; Dinh-Nhan Le; Du Duong Bui (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The climate change and global warning have been appeared as an emerging issue in recent decades. In which, the drought problem has been influenced on economics and life condition in Vietnam. In order to solve this problem, in this paper, we have designed and deployed a long range and energy efficient drought monitoring based on IoT (Internet of Things) for real time applications. After being tested in the real condition, the proposed system has proved its high dependability and effectiveness. The system is promising to become a potential candidate to solve the drought problem in Vietnam.